2012
DOI: 10.1111/j.1574-695x.2011.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal mast cells in the gastrointestinal tract are a target of staphylococcal enterotoxin type A

Abstract: Staphylococcal enterotoxin A (SEA) is a leading causative toxin of staphylococcal food poisoning. However, it remains unclear how this toxin induces emesis in humans, primates, and certain experimental animals. To understand the mechanism of SEA-induced emesis, we investigated the behavior of SEA in the gastrointestinal (GI) tract in vivo using the house musk shrew (Suncus murinus). Immunofluorescence of GI sections showed that perorally administered SEA translocated from the lumen to the interior tissues of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…The cloning and preparation of recombinant SEA and SET have been described elsewhere (5,17). To construct the recombinant SElY expression plasmid, PCR primers including the BamHI and EcoRI sites were designed to amplify a fragment of the sely gene corresponding to the mature form of SElY ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The cloning and preparation of recombinant SEA and SET have been described elsewhere (5,17). To construct the recombinant SElY expression plasmid, PCR primers including the BamHI and EcoRI sites were designed to amplify a fragment of the sely gene corresponding to the mature form of SElY ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that SEA interacts to the mast cells in the submucosa of the stomach and duodenum (Ono et al . ). However, our result demonstrated that SEA remains in the portion of mucus and does not translocate into the mucosa of the gastric loop.…”
Section: Discussionmentioning
confidence: 97%
“…).In addition, 5‐HT‐containing mast cells in the submucosa of stomach and duodenum undergo degranulation from 30 to 90 min after PO administration of SEA (Ono et al . ). From these results, it is hypothesized that SEA can translocate across the gastrointestinal mucosal barrier rapidly after PO administration.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is because the suncus has ability to vomit in response to mild shaking or chemicals . In the suncus, moreover, serotonin that is released from submucosal mast cells in the stomach and duodenum stimulated by a bacterial toxin plays an important role in toxin‐induced emesis …”
Section: Introductionmentioning
confidence: 99%